2016
DOI: 10.1039/c5tx00237k
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial protective effects of 2-allyl amino 4-methyl sulfanyl butyric acid on glucose metabolism and glycoprotein components in streptozotocin induced diabetic rats with molecular modeling

Abstract: In the present study, the potential effects of 2-allyl amino 4-methyl sulfanyl butyric acid (AMSB) on the glucose metabolism and glycoprotein components in streptozotocin (STZ) induced experimental diabetic rats were determined. Further, molecular modeling was performed to investigate the modes of AMSB interaction with insulin receptor active sites. The blood glucose and plasma insulin levels were measured in the STZ induced diabetic rats, whereas the glucose metabolism and glycoprotein components were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Protein preparation and ligand preparation have been performed for this analysis by using YASARA software, 35 which includes water removal, binding site identification, simulation box generation and energy minimization. 38 Molecular docking analysis demonstrates the best binding conformations between the receptor and ligand with the best binding energy which can be calculated using the following equation: 27…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein preparation and ligand preparation have been performed for this analysis by using YASARA software, 35 which includes water removal, binding site identification, simulation box generation and energy minimization. 38 Molecular docking analysis demonstrates the best binding conformations between the receptor and ligand with the best binding energy which can be calculated using the following equation: 27…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Steroidogenesis is a complex multi-enzyme process by which cholesterol is converted to biologically active steroid hor- 38,[49][50][51][52] by the formation of reactive oxygen species. [14][15][16] The oral administration of BPA for 45 days (groups III-V) caused a significant ( p < 0.05), dose-dependent decrease in total lipid (r = 0.722) and cholesterol contents (r = 0.971) as compared to the vehicle control group II.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…glycohybrid structures and their α-glucosidase inhibition potential were examined [27]. In addition, Balan et al (2015) [28] reported that they synthesized 2-allyl amino 4-methylsulfanyl butyric acid as a new molecule for inhibition of alpha amylase and α-glucosidase, and they carried out both molecular modeling studies and enzyme kinetic studies to evaluate the inhibition potential of the said molecule. In a previous study, molecular modeling revealed the molecular basis of the specific binding of different alpha amylase inhibitors obtained from the seeds of Phaseolus vulgaris and Alpina nigra to the active site of the enzyme [29][30][31].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…In a study, molecular modeling was used for investigating the modes of 2-allyl amino 4-methyl sulfanyl butyric acid interaction with active sites of insulin receptor. It was found that administration of 2-allyl amino 4-methyl sulfanyl butyric acid (170 mg kg −1 ) significantly decreased the glycoprotein levels of plasma, liver, and kidney whereas levels of plasma insulin, hexokinase, glycogen and glycogen synthase were potently increased [227].…”
Section: -Allyl Amino 4-methyl Sulfanyl Butyric Acidmentioning
confidence: 99%